IMPACT OF CLIMATE CHANGE ON WATER AVAILABILITY FOR AGRICULTURE IN THE MIZQUE RIVER BASIN (International Seven Journal of Multidisciplinary, 2025)
Agriculture, whether low or dry, depends heavily on climatic stability, in particular on the amount of rain and temperatures, factors that are significantly affected by climate change. These changes affect both natural ecosystems and agricultural producers dependent on water resources, as agricultural production is closely linked to evapotranspiration, which increases with higher temperatures. In semi-arid areas such as the basin of the Mizque River, most of the rainwater is lost due to evaporation, resulting in low productivity of rainwater. The main objective of the investigation was to determine the availability of the water resource in the basin of the Mizque river below the climatic scenarios: one of the baseline and the other of climatic change. For this purpose, historical climate data was compiled and projections were generated for the year 2050 using the MIROC5 climate model, selecting the most critical RCP 8.5 scenario. The data was processed and interpolarized to represent them at the level of subcuencas, and the Crawford hydrological model was used to quantify water supply (monthly dimming), while agricultural demand was estimated using the CROPWAT software. Finally, the role of water storage structures (water storage structures) in the balance between supply and demand was evaluated, and their possible contribution in a context of climate change. The investigation thus establishes a solid methodological basis to analyze the vulnerability and adaptation of the agricultural sector to climate variations in the future, offering useful tools for water management and planning in regions of high environmental and socioeconomic sensitivity.